Perubahan Preferensi Penghuni Terhadap Aspek Lingkungan Pada Perumahan Rawa Urug - Widya Fransiska F Anwar (Unika Soegijapranata Semarang, 2018)
Palembang is a river city that its land is dominated by lowland. In its initial development, the settlement was built based on adaptation to the nature of lowland area such as riverbanks and marsh. Along with the increasing population, the settlements including housing area has spread from landed to lowland area. Many housing areas are developed on the reclaimed low lying land. The problem has arisen when the flood happened in this housing area. The flood has affected residents’ well-being and image of housing area as elite estate. The aim of this paper is to evaluate the preference of residents on the environment of housing on the reclaimed lowland area. To achieve this aim, the study examines the change of preference of residents on three aspects; housing attributes, renovation and infrastructure quality. The study used quantitative method. Data were collected by survey questionaire from 150 residents. Data were analyzed by using factor analysis. The results show that there is a change ofresident preference from housing attributes to the environmental aspects, particularly the quality of drainage system and the availability of water catchment area. This change appears after the flood happened recently in their housing area as an impact of the reclaimation. Study concludes that the water management system is the aspect for controlling the inevitable city development at lowland area.